Fieldwork under fire : contemporary studies of violence and survival - Nordstrom, Carolyn, 1953-; Robben, Antonius C. G. M. (University of California Press, 1995)
This title presents a collection of essays written by anthropologists who have experienced the unpredictability and trauma of political violence firsthand. These essays combine theoretical, ethnographic, and methodological points of view to illuminate the processes and solutions that characterize life in dangerous places.